Draft Genome Sequence of Salmonella enterica subsp. enterica Serovar Blockley Strain CRJJGF_00147 (Phylum Gammaproteobacteria) - Gupta, Sushim K. (Genome Announc, 2016)
Here, we report a 4.72-Mbp draft genome sequence of Salmonella enterica subsp. enterica serovar Blockley strain CRJJGF_00147, isolated from chicken rinse in 2009.